The Urinary Tract A Comprehensive Guide to Patient Diagnosis and Management - Hansel, Donna E.; Hansel, Donna E.; McKenney, Jesse K.; McKenney, Jesse K.; Stephenson, Andrew J.; Stephenson, Andrew J.; Chang, Sam S.; Chang, Sam S. (Springer New York : Imprint: Springer, 2012)
Providing a true integration of pathology with clinical management, this volume presents a practical, comprehensive text on benign and malignant disease of the adult bladder. Integrating pathology, surgical management, oncology and molecular study in a site-specific manner to include the urethra, urinary bladder, ureter and renal pelvis, The Urinary Tract: A Comprehensive Guide to Patient Diagnosis and Management is the first text in adult bladder disease to closely interweave multiple clinical disciplines into each chapter. For the majority of chapters, a pathologist and urologist or urologic oncologist are paired to provide the greatest integration of information for each disease process.